Developing a patient satisfaction measure for imaging-based patient information during clinical consultations - Hindrik Pinkster; Anne Meesters; Frank IJpma; Erik Taal; Joep Kraeima; Peter Ten Klooster (The Beryl Institute, 2022)
Different types of medical imaging are increasingly being used to explain specific aspects of injuries to patients during consultations. However, there are no validated questionnaires available yet that specifically measure patients' satisfaction with the use of such images. The objective of this study was to develop and evaluate a patient-centred measure of satisfaction with the use of medical imaging modalities in clinical treatment. A preliminary 22-item version of the Questionnaire for Patient Satisfaction with Imaging (QPSI) was developed based on extant literature and interviews with trauma patients. Final item selection and psychometric evaluations were conducted amongst a sample of 106 hospital trauma patients who were shown medical images of their injuries. The psychometric analyses resulted in a final 13-item questionnaire comprising two subscales that measure the importance of seeing the images (9 items) and the clearness of the image (4 items). Both subscales showed adequate internal consistency (α = 0.84 and 0.75). The subscales were weakly intercorrelated (ρ = 0.34) and were both significantly and independently associated with patients' global ratings of satisfaction with the use of imaging. The final two-dimensional QPSI is an innovative, reliable and valid questionnaire for measuring patients' satisfaction with imaging-based information during clinical consultations. Experience Framework This article is associated with the Quality & Clinical Excellence lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Quality%20%26%20Clinical%20Excellence%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.